2016
DOI: 10.1186/s40249-016-0126-9
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niches and blood sources of sand fly in an endemic focus of visceral leishmaniasis in Jiuzhaigou, Sichuan, China

Abstract: BackgroundSand fly Phlebotomus chinensis is a principle vector for the visceral leishmaniasis (VL) in China with a wide geographic distribution. Jiuzhaigou, Sichuan is a mountain type endemic area of VL in China. Long term effective control efforts in the region have successfully reduced VL transmission. To assess the current status of the sand flies and their ecological aspects in the region, a survey was conducted in the summer of 2014 and 2015.MethodsSand fly specimens were collected by light traps in a vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…The results showed that the chickens and humans were the most common blood sources of sand ies in the extension region of the Loess Plateau, China, while dogs, goats, cattle and pigs were also blood sources. In Jiuzhaigou Sichuan, China, swine was the dominant blood source of sand ies, followed by chickens and dogs [22]. The results do not support the generally accepted opinion that humans and dogs are preferred feeding host of Ph.…”
Section: Comprehensive Detections From Yangquanmentioning
confidence: 63%
See 1 more Smart Citation
“…The results showed that the chickens and humans were the most common blood sources of sand ies in the extension region of the Loess Plateau, China, while dogs, goats, cattle and pigs were also blood sources. In Jiuzhaigou Sichuan, China, swine was the dominant blood source of sand ies, followed by chickens and dogs [22]. The results do not support the generally accepted opinion that humans and dogs are preferred feeding host of Ph.…”
Section: Comprehensive Detections From Yangquanmentioning
confidence: 63%
“…The individual samples include 118 from YQ and 108 from WX. The mtDNA cyt b fragments of different animals and human were ampli ed by PCR [19][20][21][22]. According to the main animal species in the collection site, PCR assay was developed with primers speci c to human, chicken, goat, pig, cattle and dog.…”
Section: Blood Sources Identi Cationmentioning
confidence: 99%
“…They take blood mostly from mammals [20,[30][31][32][33] and cold-blooded animals [21]. In Jiuzhaigou Sichuan, China, swine was the dominant blood source of sand ies, followed by chickens and dogs [22]. However, there has been no report concerning the blood sources of sand ies in extension region of the Loess Plateau, China.…”
Section: Comprehensive Results Of Yangquanmentioning
confidence: 99%
“…Various studies, notably from South America and Asia, report that pigs appear to be among the preferred hosts for certain sand fly species [77][78][79][80]. A study in China reported high numbers of engorged sand flies on pigs and hypothesized that soil enriched with organic matter in pig pens could be an appropriate substrate for their larval development [81]. However, it should be noted that all these studies concern exotic sand fly species that are absent from Europe.…”
Section: Phlebotominaementioning
confidence: 99%